A less or Little Known Plant of Eastern Himalaya - Ghosh, R. B.; Rao, R. S.; Maity, G. G. (Indian Forester, 1978)
Primula bhutanica Fletcher, a less or little known plant of Eastern Himalaya and a very confusing species collected after 38 years has been described with an illustration.